The impact of Septoria tritici blotch in bread making quality among argentinean wheat cultivars - Castro, Ana Carolina (2017)
Septoria tritici blotch (STB), caused by Zymoseptoria tritici is a relevant foliar wheat disease worldwide. Several reports show the importance of STB on grain yield, their components and grain protein while little is known about its effect on the rheological properties of the wheat flour. The scarce literature found, only mentions the effect of the complex of foliar diseases on wheat quality, without individualizing the effect of the different pathogens separately. This study analyze the influence of increasing doses of inoculum of Zymoseptoria tritici, on the bread making quality of ten Argentinean wheat cultivars and its possible variation according to their quality group. The increase of inoculum concentration augmented the area under disease progress curve, decreased green flag leaf area duration and green leaf area duration. Cultivars K. Flecha and B.75 Aniversario had the lowest green flag leaf area duration causing higher reduction in grain filling period and higher reductions in P, indicating a lower gliadin/glutenin ratio. STB decreased P/L and E while L, W, D, SV and bread volume increased. Cultivars differed in rheological parameters according to their quality group. Gluten/protein relationship was significant in quality group 1 and non-significant in cultivars belonging to quality group 2 and 3.